Privatgrün 1994 : 21 Skulpturen und Installationen von 21 Bildhauern/innen in 21 Kölner Privatgärten. - Kolberg, Gerhard; Schneckenburger, Manfred (Köln : Kunstraum Fuhrwerkswaage, 1994)
Bandau, Joachim ; Brummack, Heinrich ; Bury, Claus ; Friedmann, Gloria ; Frisch, Mechtild ; Fritsch, Lutz ; Hien, Albert ; Isenrath, Hans-Paul ; Kaiser, Kirsten ; Keusen, Ellen ; Lauer, Anette ; Löbbert, Maik & Dirk ; Nierhoff, Ansgar ; Nolte, Faustinus ; Pallanca, Heike ; Prager, Heinz-Günter ; Reineking, James ; Reusch, Erich ; Simon, Klaus ; Telljohann, Peter ; Wagner K., Matthias
biog. p. 150-151
Duits
Privatgrün 1994, Kunstraum Fuhrwerkswaage, Köln, Mai 1994
boek
Keywords: Köln